NBS‐Mediated Oxygen Transfer Reaction of Carbonyl in Ester: Efficient Synthesis of Benzil–o‐carboxylate Derivative From o‐Alkynylbenzoate. Issue 11 (13th April 2017) - Yuan, Si‐Tian; Wang, Yan‐Hua; Liu, Jin‐Biao; Qiu, Guanyinsheng
Abstract: A neighbouring ester group‐participated diketonization of o‐alkynylbenzoate is described here for the synthesis of benzil‐o‐carboxylate. Application of the resulting benzil‐ o ‐carboxylate in the synthesis of quinoxalines is also reached from o‐alkynylbenzoate in an one‐pot fashion. This diketonization proceeds smoothly with a high regioselectivity under mild conditions. Importantly, neighbouring group plays an important role in diketonization. A plausible mechanism suggests that a bromo‐incoporated isocoumarin cation is described as an intermediate, and the whole process is constituted by NBS‐mediated electrophilic 6‐ endo annulation and oxygen transfer reaction through NBS‐mediated oxidative ring‐opening. Water serves as a nucleophile of ring‐opening. Abstract :